Beneficial effects of non-invasive physical plasma on human periodontal ligament cells in vitro - Eggers, Benedikt; Seher, Lennard; Marciniak, Jana; Pauck, Tristan; Deschner, James; Eick, Sigrun; Stope, Matthias Bernhard; Kramer, Franz-Josef; Küchler, Erika Calvano; Kirschneck, Christian; Nokhbehsaim, Marjan; Beisel-Memmert, Svenja (Frontiers in Medicine, 2024)
Introduction Periodontitis is a chronic inflammatory disease of the periodontium that can lead to the loss of affected teeth if left untreated. It is induced by a multifactorial process centered on microbial pathogens such as Fusobacterium nucleatum (F.n.). Non-invasive physical plasma (NIPP), a highly reactive gas, has become a focus of research, not only for its hemostatic, proliferation-enhancing and apoptotic properties, but also for its antimicrobial potential. The objective of this study was to examine the impact of NIPP on human periodontal ligament (PDL) cells that had been induced into a state of periodontal infection in vitro. Methods Initially, the solitary effect of NIPP was evaluated by measuring temperature and pH and analyzing reactive oxygen species (ROS). Additionally, DAPI and phalloidin staining were employed to investigate possible cytotoxic effects. The cells were pre-incubated with F.n. and treated with NIPP after 24 hours. Interleukin (IL)-6 and IL-8 were analyzed at mRNA and protein levels, respectively, by real-time PCR and ELISA. Results NIPP alone had no significant effect on PDL cells. However, the F.n.-induced upregulation of IL-6 and IL-8 was counteracted by NIPP. Discussion Thus, the utilization of NIPP may be regarded as a promising therapeutic strategy for the treatment of periodontal diseases.